Efectos de los ejercicios isométricos en el tratamiento de artrosis de rodilla en pacientes geriátricos que acuden al Centro de Rehabilitación Lenin Moreno, San Juan, periodo octubre 2024- abril 2025. - Fernández Chenlan, Eva Tahily (2025)
Knee osteoarthritis is a degenerative condition in the cartilage that significantly affects the tissues that become very common with aging, causing pain and reduction in mobility. Its incidence worldwide has increased with the aging of the knee. Population, is one of the main causes. In Ecuador, the incidence is higher in women, considered 80% of people over 65 years of age who demonstrate knee osteoarthritis. In the San Juan parish at the Lenin Moreno Rehabilitation Center between October 2024 and April 2025, a descriptive, inductive, and field study was undertaken that included 80 patients with a diagnosis of knee osteoarthritis, of which 64 were collected as sample, under inclusion and exclusion criteria. The results revealed that the cause such as age, knee injuries, are significantly related to the development of the disease, this research will not only benefit patients, it will also serve as a tool to implement new physiotherapy exercise programs. Based on the discovery, it is proposed to determine isometric exercises that reduce pain, increase functionality and provide an applicable exercise model, improving the quality of life of the elderly, particularly in the aging stage.